2019
DOI: 10.1037/edu0000332
|View full text |Cite
|
Sign up to set email alerts
|

Examining sources and mechanisms of reading comprehension difficulties: Comparing English learners and non-English learners within the simple view of reading.

Abstract: In the present study, we compared the extent to which linguistic comprehension (vocabulary and listening comprehension) and word reading explain reading comprehension differentially for English learners (ELs) and non-ELs with reading difficulties, and we investigated whether different mechanisms of reading comprehension failure exist for each group. Using the simple view of reading as our framework, we tested a model in which vocabulary exerts a direct effect on reading comprehension and indirect effects throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
73
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(81 citation statements)
references
References 131 publications
(269 reference statements)
8
73
0
Order By: Relevance
“…In a meta-analysis of comprehension problems for ELL poor comprehenders, Spencer and Wagner (Spencer & Wagner, 2017) reported a substantial difference in oral language skills including vocabulary breadth between ELLs with and without reading comprehension deficits. Relatedly, vocabulary and listening comprehension have been shown to explain more variance in reading comprehension in ELLs with reading comprehension difficulties than in EL1s with reading comprehension difficulties (Cho et al, 2019). Taken together, the research evidence indicates that vocabulary, listening comprehension, and morphological awareness are potential sources of difficulties for ELL poor comprehenders in the upper elementary grades.…”
Section: The Reading Profile Of Ell Poor Comprehendersmentioning
confidence: 77%
See 1 more Smart Citation
“…In a meta-analysis of comprehension problems for ELL poor comprehenders, Spencer and Wagner (Spencer & Wagner, 2017) reported a substantial difference in oral language skills including vocabulary breadth between ELLs with and without reading comprehension deficits. Relatedly, vocabulary and listening comprehension have been shown to explain more variance in reading comprehension in ELLs with reading comprehension difficulties than in EL1s with reading comprehension difficulties (Cho et al, 2019). Taken together, the research evidence indicates that vocabulary, listening comprehension, and morphological awareness are potential sources of difficulties for ELL poor comprehenders in the upper elementary grades.…”
Section: The Reading Profile Of Ell Poor Comprehendersmentioning
confidence: 77%
“…Since inherent differences exist between ELLs and EL1s, it is not clear whether the results of studies involving EL1 poor comprehenders can be generalized to ELL poor comprehenders. For example, Cho, Capin, Roberts, Roberts, and Vaughn (Cho, Capin, Roberts, Roberts, & Vaughn, 2019) found that vocabulary knowledge and listening comprehension each explained a larger proportion of variance in reading comprehension for ELLs with reading comprehension difficulties than their EL1 counterparts.…”
Section: The Present Studymentioning
confidence: 99%
“…Cross-sectional studies conducted with monolingual and language-learning upper elementary students in Canada (Grant, Gottardo, & Geva, 2011), the United Kingdom (Babayiğit, 2014), the Netherlands (e.g., Droop & Verhoeven, 2003), and the United States (Cho, Capin, Roberts, Roberts, & Vaughn, in press) suggest that vocabulary knowledge and other linguistic comprehension variables may make a greater contribution to reading comprehension for EL students than for EO students in the upper elementary and secondary grades. In the study conducted by Cho et al (in press) with participants who were ELs with significant reading difficulties, linguistic comprehension variables made a greater contribution to reading comprehension than word reading variables, while the opposite pattern held true for EO students. These cross-sectional findings align with other research suggesting that specific reading comprehension difficulties may be more prevalent in populations of ELs than in populations of monolingual students (Lesaux, 2006; Lesaux & Kieffer, 2010; Nakamoto, Lindsey, & Manis, 2007; Spencer & Wagner, 2017).…”
Section: Reading Comprehension and English Learners (Els)mentioning
confidence: 91%
“…Developmental dyslexia is a specific learning (reading) disorder characterized by problems with coping with written symbols despite normal intelligence (Davis, n. d.;Snowling, 2015;Thompson et al, 2015). Not only do problems occur in the reading process, everyday life quality is also affected (Cho, Capin, Roberts, Roberts G., J., & Vaughn, 2019). Dyslexic children and adults may have problems putting things in order, following instructions, may confuse left and right, and other manifestations.…”
Section: Theoretical Framework and Findings In Scientific Literaturementioning
confidence: 99%